PERBEDAAN SPESIFIC VALUES ANTARA MAHASISWA AKUNTANSI, MANAJEMEN, DAN EKONOMI PEMBANGUNAN : STUDI EMPIRIS PADA UNIVERSITAS PATTIMURA - Trisna Sary Lewaru (Universitas Negeri Yogyakarta, 2020)
This study aims to analyze, to compare and to differentiate specific values of accounting, management, development economic. While the majority of previous studies used the Rokeach instrument survey, the current study employs the modified Rokeach and Schwartz Instrumen. Factor analysis indicates that the variables can be grouped into four constructs: individuality, theoretical, social, and esthetical. Overall. The study shows that there are significant differences in the value of indivualis, theoretical, social, and esthetical, among accounting, management, development economic students.